2016
DOI: 10.1007/s11356-016-7415-5
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of illicit drugs and selected pharmaceuticals in Slovak municipal wastewater

Abstract: We analyzed illicit drugs and their metabolites and pharmaceuticals in wastewater from 15 selected wastewater treatment plants (WWTPs) in Slovakia. Our results indicate that methamphetamine is one of the most commonly used illegal drugs in all the regions of Slovakia monitored in this study. Compared with the international results, the Slovak cities of Dunajská Streda (479 mg/day/1000inh) and Trnava (354 mg/day/1000inh) are among the cities with the largest numbers of methamphetamine users in Europe. These res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 17 publications
0
10
0
2
Order By: Relevance
“…Sartans are mostly excreted as parent compounds, with percentages of metabolization below 25% (Bayer et al, 2014). Consequently, they are present in urban sewage water at concentrations in the ng per mL -1 range (Bodík et al, 2016;Oosterhuis et al, 2013;Stankiewicz et al, 2015). Their mass balances in conventional sewage treatment plants (STPs), equipped with primary and activated sludge units, showed variable, yet incomplete removal efficiencies.…”
Section: Introductionmentioning
confidence: 99%
“…Sartans are mostly excreted as parent compounds, with percentages of metabolization below 25% (Bayer et al, 2014). Consequently, they are present in urban sewage water at concentrations in the ng per mL -1 range (Bodík et al, 2016;Oosterhuis et al, 2013;Stankiewicz et al, 2015). Their mass balances in conventional sewage treatment plants (STPs), equipped with primary and activated sludge units, showed variable, yet incomplete removal efficiencies.…”
Section: Introductionmentioning
confidence: 99%
“…By contrast, methamphetamine use remained relatively steady throughout a week and was remarkably similar across study sites, except for a few large cities that had elevated use. Bodík et al (2016) found that methamphetamine was the most commonly used illegal drug in all the regions of Slovakia monitored in their study. The highest 2year mean concentrations of THC-COOH, a cannabis biomarker, were measured in the sewage from two of the monitored cities to be 191 and 171 ng/L, respectively.…”
Section: Full-scale Experimental Activitymentioning
confidence: 88%
“…The current state of knowledge on their occurrence, transportation, distribution and transformation in water bodies and ambient air is still incomplete. It is known that, after legal or illegal consumption, drugs and their metabolites are excreted in urine, faeces, saliva or sweat (Bodík et al 2016). Then, they enter sewage network through which are transferred to the wastewater treatment plants (WWTPs).…”
Section: Introductionmentioning
confidence: 99%
“…Con los informes del consumo de COC de los artículos fue posible calcular que tanto la COC como su principal metabolito urinario, la BE, el consumo promedio en torno a 230 (mg/día)/(1000 personas). Esto equivale a, aproximadamente dos dosis diarias entre 1000 personas, suponiendo que la dosis de referencia de COC es de 100 mg 52 , para el metabolito del cannabis varía entre 108 -133 (mg/día)/(1000 personas) [34][35][36][38][39][40]41,44,45,48,[56][57][58] .…”
Section: Descripción Y Análisis De Los Artículosunclassified
“…Bodík, et al 34 Eslovaquia Se analizaron las drogas ilícitas y sus metabolitos y productos farmacéuticos en aguas residuales de 15 plantas de tratamiento de aguas residuales. Los resultados confirman las estadísticas policiales sobre producción y uso de drogas ilícitas en Eslovaquia.…”
Section: Fuentes Y Distribución En El Medio Ambienteunclassified